A oferta do ensino bilíngue na rede estadual de ensino do Amazonas: a realidade de uma escola de ensino médio - Rocha, Maria Júlia Oliveira (BRASIL, 2024)
The study analyzes the provision of bilingual education in the state education network of Amazonas, analyzing academic production on the topic of bilingual education and verifying the process of implementing bilingual secondary education by a secondary school located in Manaus. The methodology of a documentary nature, within a qualitative approach, enabled the analysis of official documents that standardize and guide the bilingual education policy in the state network, including legislation and school documents such as the Political-Pedagogical Project of a school of the state network that offers bilingual secondary education. It also prioritized the survey of recent academic production of theses, dissertations and articles in the area of ​​education. The results indicate that the process of implementing bilingual schools is surrounded by uncertainty from a normative point of view and there is a need for further studies in the area of ​​education on this topic, especially with regard to public schools that have joined this movement of offering the so-called bilingual teaching.